Análisis de las Competencias Profesionales para el perfeccionamiento del Perfil Profesional de los estudiantes de Cuarto Semestre de la Carrera de Biología, Química y Laboratorio, período 2016- 2017 - Miñarcaja Llangari, Silvia Maribel (2018)
This research was conducted in Human Science And Technology Education College, at Chemical Biology and Laboratory major – Fourt Semester, From September 2016 to march 2017. Pre- professional competences were analyzed which allowed seeing that there is a lack of professional profile strengthening in university students currently. At is observed, students were not able to solve problems related to daily life and education context at all. Therefore, this research objective was to analyze, if the current and learned professional competences contribute to professional profile autput. The research was based on authors such as Jerome bruner and jean piaget. Particularly, piaget’s constructivism theory since it is based on learnig construction thronugh self- discovery by doing hands –on activiyties. Theresearch. Designwas non- experimental because variables were not manipulated, actually, it is a field research. The research methods were inductive deductive. Its population was 18 students. For gathering information surveys were applied, including their tabulation later on the conclusions and recommendation were establinshed. To sum up, it is concluded that the learned competences are not meaningful in the teaching profession field. It means that they are not the ideal ones for accomplishing education demands.